BASIC FUNDS ANALYSIS OF DOING IMPORTANCE OF THE MARKET - S.N.Xadjibekov; I.B.Sapayev; S.Sh.Tashibekova; A.X.Xolbozorov; Y.Y.Temirov; Z.B.Qobulova; J.B.Karimbayev; G.U.Masheripova (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
In the conditions of market relations, the essence and purpose of economic analysis has changed fundamentally. The financial and management analysis will be conducted in view of the purpose and benefit of the enterprise, its development and effective use of its resources. In this regard, there is a need to analyze the activities of enterprises in the market economy.